Students’ evaluation in the developed video-based learning materials for physical education in Higher Education Institutions (HEIs) - Aquino, John Michael (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
Higher Education Institutions (HEIs) are urged to integrate technology and improve their digital skills in response to the changing overall trend and issues in the educational system. The service physical education course in college refers to four (4) topics required in the first four (4) semesters, which includes Physical Education- Rhythmic Activities. In line with this, the researcher was inspired to develop a video-based learning material for first-year students. The research study aimed to evaluate the developed learning materials by parts and characteristics. The researcher utilized the method of descriptive-evaluative research design and a self-made survey type-questionnaire was employed through an online web provider with a total of 130 students’ respondents with the used of purposive sampling. The validation and reliability of the questionnaire were also utilized and showed the 0.8284 Cronbach alpha which was good. The learning material was described by the respondents in terms of learning objective, content, and application. On the other hand, the evaluation of the learning materials in terms of usability, consistency, versatility, and aesthetic value was observed by the respondents. The findings illustrated that the overall assessment of the students’ respondents in all indicators on the Video-Based Learning Materials are highly acceptable based on their experiences while they are using the materials. This can be utilized by the 1st year students of Higher Education Institutions, revisions still consider in the development of the learning material, and validation may be done on the level of difficulty of the applications and simulations.